On a Few RItuals and Various Demons - Mladen Stajić (Etnoantropološki Problemi, 2014)
On the Book by Danijel Sinani, Demons and Rituals: Periodical Rituals and Demonology of Serbian Traditional Religion. Beograd. Srpski geneaološki centar, 2013.